Understanding fundamental principles of enhancer biology at a model locus: analysing the structure and function of an enhancer cluster at the α-globin locus - Kassouf, M; Ford, S; Blayney, J; Higgs, D (Wiley, 2023)
Despite ever-increasing accumulation of genomic data, the fundamental question of how individual genes are switched on during development, lineage-specification and differentiation is not fully answered. It is widely accepted that this involves the interaction between at least three fundamental regulatory elements: enhancers, promoters and insulators. Enhancers contain transcription factor binding sites which are bound by transcription factors (TFs) and co-factors expressed during cell fate decisions and maintain imposed patterns of activation, at least in part, via their epigenetic modification. This information is transferred from enhancers to their cognate promoters often by coming into close physical proximity to form a 'transcriptional hub' containing a high concentration of TFs and co-factors. The mechanisms underlying these stages of transcriptional activation are not fully explained. This review focuses on how enhancers and promoters are activated during differentiation and how multiple enhancers work together to regulate gene expression. We illustrate the currently understood principles of how mammalian enhancers work and how they may be perturbed in enhanceropathies using expression of the α-globin gene cluster during erythropoiesis, as a model.